2023
DOI: 10.1177/23821205231178449
|View full text |Cite
|
Sign up to set email alerts
|

Practical Applications of ChatGPT in Undergraduate Medical Education

Abstract: ChatGPT is a chatbot developed by OpenAI that has garnered significant attention for achieving at or near a passing standard on the United States Medical Licensing Exam (USMLE). Currently, researchers and users are exploring ChatGPT's broad range of potential applications in academia, business, programming, and beyond. We attempt outline how ChatGPT may be applied to support undergraduate medical education during the preclinical and clinical years, and highlight possible concerns regarding its use which necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 24 publications
0
33
0
2
Order By: Relevance
“…In this study, a slightly less than a quarter of the participating students indicated the use of ChatGPT highlighting the widespread adoption of this LLM-based tool, previously recognized as the most rapidly expanding consumer application in history [56][57][58]. This versatility of ChatGPT use or the intention to use it as an aid in university assignments was illustrated recently in a large multinational study by Ibrahim et al [59].…”
Section: Discussionmentioning
confidence: 54%
“…In this study, a slightly less than a quarter of the participating students indicated the use of ChatGPT highlighting the widespread adoption of this LLM-based tool, previously recognized as the most rapidly expanding consumer application in history [56][57][58]. This versatility of ChatGPT use or the intention to use it as an aid in university assignments was illustrated recently in a large multinational study by Ibrahim et al [59].…”
Section: Discussionmentioning
confidence: 54%
“…In this study, a slightly less than a quarter of the participating students indicated the use of ChatGPT highlighting the widespread adoption of this LLM-based tool, previously recognized as the most rapidly expanding consumer application in history [57][58][59] . This versatility of ChatGPT use or the intention to use it as an aid in university assignments was illustrated recently in a large multinational study by Ibrahim et al 60 .…”
Section: Discussionmentioning
confidence: 98%
“…In medical education, ChatGPT could be used in various aspects [27]. Using ChatGPT for preparing for OSCE and other exams was mentioned by participants and in the literature [28]. For OSCE, it could help by generating example scenarios, suggesting a proper physical examination, and giving appropriate medical advice.…”
Section: Discussionmentioning
confidence: 99%